Immunohistochemical Expression of Haptoglobin in Skin Lesions of Hidradenitis Suppurativa - Nessr Abu Rached; Hanna Telkemeyer; Marina Skrygan; Martin Doerler; Yannik Haven; Lennart Ocker; Daniel Myszkowski; Thomas Meyer; Markus Stücker; Eggert Stockfleth; Falk G. Bechara (Life)
Background: Meta-inflammation is a hallmark of hidradenitis suppurativa (HS). Research on meta-inflammation in HS is growing, but there is still no research on haptoglobin as an inflammatory protein in lesional HS skin. This study examines the relationship between haptoglobin expression in HS skin lesions and clinical parameters. Methods: An examination was performed on 44 skin samples from HS patients and 10 healthy skin samples. Clinical parameters were then compared with haptoglobin expression. Results: Median haptoglobin expression was significantly higher in the Hurley stage III lesions compared with milder stages (H-score: 37.6 versus 17.1, p = 0.028). High haptoglobin expression (≥30.8% positive cells) was associated with advanced disease (Hurley stage III: 80% versus 41.7%, p = 0.01), active smoking (80% versus 50%, p = 0.039), increased pain (visual analogue scale: 5 versus 1.5, p = 0.03), and a higher prevalence of diabetes (35% versus 8.3%, p = 0.029) and hypertension (55% versus 25%, p = 0.042). No significant associations were found with the BMI, disease duration, or CRP levels. Conclusions: High haptoglobin expression (positive cells ≥ 30.8%) in a skin lesion is associated with higher HS severity, active smoking, more pain and the comorbidities of diabetes mellitus and arterial hypertension in HS patients.